TIGA WUJUD PELAYANAN DALAM â€œPORTAL EMASâ€ SEBAGAI WUJUD E-GOVERMENT DENGAN PRINSIP ETIKA ADMINISTRASI NEGARA (ANALISIS PELAYANAN LISAN, TULISAN, DAN TINDAKAN DI KOTA PROBOLINGGO) - Supriyanto, Supriyanto; Lailatul Fitria, Nurul Jannah; Hidayat, Sahrul (Universitas Islam Malang, 2022)
The government has responsibility for public sector services. The public services are intended to provide convenience and assistance to the public regarding what they need and to achieve an objective. Public services must understand and meet the community's needs regarding services, goods, and administration that need to be carried out properly. The forms of service can be verbal or written, or direct action. The governments, both local and central governments, need to improve the quality of service delivery. Therefore, the Probolinggo City Government had a strategy of providing quality public services. This public service innovation was called the